Age Relationships of Laurentide and Montane Glaciations, Mackenzie Mountains, Northwest Territories - Duk-Rodkin, Alejandra; Hughes, Owen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTThe Mackenzie Mountains were glaciated repeatedly by large valley glaciers that emanated from the Backbone Ranges, and by much smaller valley glaciers that emanated from peaks in the Canyon Ranges. During the Late Wisconsinan the Laurentide Ice Sheet reached its all-time maximum position. The ice sheet pressed against the Canyon Ranges and moved up major valleys causing the diversion of mountain waters and organizing a complex meltwater system that drained across mountain interfluve areas towards the northwest. Two ages of moraines deposited by montane glaciers occur widely in the Mackenzie Mountains. Near the mountain front certain of the older moraines have been truncated by the Laurentide Ice Sheet, and others have been incised by meltwater streams emanating from the Laurentide ice margin, indicating that these older moraines predate the maximum Laurentide advance. Locally, certain of the younger montane moraines breach moraines and other ice marginal features of the Laurentide maximum, indicating that the younger montane glaciation post-dated the Laurentide maximum. Some large montane glaciers extended out from the mountains to merge with the retreating Laurentide Ice Sheet. There are several localities that display the age relationships between montane and Laurentide glaciations such as Dark Rock Creek, Durkan-Lukas Valley, Little Bear River and Katherine Creek. The older of the local montane glaciations is correlated tentatively with Reid Glaciation (lllinoian?) of central Yukon, and the younger with the Late Wisconsinan McConnell Glaciation. The Laurentide Glaciation is correlated with Hungry Creek Glaciation of Bonnet Plume Depression, which probably culminated about 30,000 years ago or somewhat later.